High-Q transmission characteristics in terahertz guided-mode magnetic resonance system - Yan, Fei; Li, Qi; Wang, Ze Wen (Frontiers in Physics, 2023)
Guided mode resonance is generated by coupling wave diffractions with the waveguided mode. The guided mode resonances provide narrow-linewidth and intensity for high quality (Q) factor optical resonators. Here, we demonstrate the high-Q guided mode resonances propagating on a low-loss, terahertz guided-mode magnetic system, which are periodic square lattices of U-shaped split ring resonators (SRRs) on quartz substrates. The dependences of the magnetic dipole resonance on the lattice period and structural parameters are investigated and discussed. By choosing a judicious array period, two distinct frequency guided mode resonances are observed. The interaction of the two resonances at similar frequencies produces a total transmission peak. The frequency difference between these two guided mode resonances widens with increasing Lattice period. The sharp spectral feature of each resonance results in the abrupt degradation of the spectral edge transmission. The proposed scheme is promising for efficient terahertz sensing, switching, and slow-light devices